2018
DOI: 10.1186/s40001-018-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound estrogen receptor alpha initiated signaling is dynamin dependent in breast cancer cells

Abstract: BackgroundAlthough membrane-associated estrogen receptors (mERs) have been known to play important role in steroid-induced signal transmission, we still know little about their function in the estrogen-induced proliferation of breast cancer cells.MethodsIn our current work we tried to separate membrane-initiated estrogen receptor signaling from the overall estrogenic effect in MCF-7 breast carcinoma cells. Re-analyzing expression data from multiple microarray experiments, we selected a set of key regulatory ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…43,44 Marczell et al have shown that the ERa pathway is linked to dynamin-dependent receptor endocytosis in MCF-7 cells. 45 Specically, immunoelectron microscopy imaging showed that membrane bound ERa undergoes ligand-mediated receptor internalisation via a dynamin-dependent pathway. 45 To demonstrate whether dynamin plays a role in ERa-AuNPs cellular uptake, MCF-7 cells were treated with dynasore, a GTPase inhibitor of dynamin.…”
Section: Era-aunps Enter Mcf-7 Cells Using Dynamin Dependent Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Marczell et al have shown that the ERa pathway is linked to dynamin-dependent receptor endocytosis in MCF-7 cells. 45 Specically, immunoelectron microscopy imaging showed that membrane bound ERa undergoes ligand-mediated receptor internalisation via a dynamin-dependent pathway. 45 To demonstrate whether dynamin plays a role in ERa-AuNPs cellular uptake, MCF-7 cells were treated with dynasore, a GTPase inhibitor of dynamin.…”
Section: Era-aunps Enter Mcf-7 Cells Using Dynamin Dependent Endocytosismentioning
confidence: 99%
“…45 Specically, immunoelectron microscopy imaging showed that membrane bound ERa undergoes ligand-mediated receptor internalisation via a dynamin-dependent pathway. 45 To demonstrate whether dynamin plays a role in ERa-AuNPs cellular uptake, MCF-7 cells were treated with dynasore, a GTPase inhibitor of dynamin. 46 The use of dynasore aimed to inform whether the inhibition of dynamin would disrupt the internalisation of ERa-AuNPs.…”
Section: Era-aunps Enter Mcf-7 Cells Using Dynamin Dependent Endocytosismentioning
confidence: 99%
“…stimulating PI3K/Akt and MAPK (mitogen-activated protein kinase) signaling intermediates [23][24][25]. The E-SCREEN assay and molecular docking studies were used to assess the estrogenic activity of samples and determined the mechanism for this through the characterization of the interaction with ERs.…”
Section: Isolation and Identification Of Compounds From P Pellucida mentioning
confidence: 99%
“…The biological activities of estrogens are mediated by both genomic and non-genomic pathways [23][24][25]. Genomic effects are those involving the migration of estrogen-receptor complexes to the cell nucleus and direct interaction with chromatin at specific DNA sequences referred to as estrogen response elements (EREs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation